ANALISIS TEORI REKRUTMEN PENDIDIK MENURUT GARY DESSLER DALAM UPAYA MELESTARIKAN BUDAYA KERJA SEKOLAH - Rahma Dwi Aqilah; Nur Halisah; Siti chadidjah (LPPM Universitas Cipta Mandiri, 2026)
The recruitment process in educational institutions is still stuck in administrative routines, oftenneglecting the strategic competencies that are actually needed. This suboptimal recruitment systemresults in suboptimal human resources, both in terms of professional competencies and alignment withthe school's work culture. In schools, this process is inefficient due to limited budgets for temporaryteachers' honoraria, which makes it difficult to retain qualified educators. The dissemination ofrecruitment information also still relies on family networks through verbal communication betweencolleagues, which severely limits its effectiveness. This study aims to analyze the concept of educatorrecruitment according to Gary Dessler's theory and examine the gap between this concept andrecruitment practices in educational institutions. This study uses a literature review method (libraryresearch) by examining books, scientific journals, and relevant policy documents. This study shows thatthe professionalism of educators is directly proportional to the effectiveness of the recruitment systemimplemented. The integration of Dessler's theory in human resource management in schools has beenproven to accelerate improvements in education quality. With a strict, competency-based recruitmentsystem, educational institutions can ensure that every educator who joins has a high level of professionaldedication. The results of this study recommend the use of Dessler's theory as a standard in the transformation of recruitment systems to create a quality, competitive, and sustainable educationecosystem.